Theory of computational complexity - Du, Dingzhu; Ko, Ker-I (Hoboken, New Jersey : John Wiley & Sons, 2014)
Praise for the First Edition "" ... complete, up-to-date coverage of computational complexity theory ... the book promises to become the standard reference on computational complexity.""--Zentralblatt MATH A thorough revision based on advances in the field of computational complexity and readers' feedback, the Second Edition of Theory of Computational Complexity presents updates to the principles and applications essential to understanding modern computational complexity theory. The new edition continues to serve as a comprehensive resource on the use of.
8.8 Relativized Probabilistic Complexity ClassesExercises; Historical Notes; Chapter 9 Complexity of Counting; 9.1 Counting Class #P; 9.2 #P-Complete Problems; 9.3 oplus P and the Polynomial-Time Hierarchy; 9.4 #P and the Polynomial-Time Hierarchy; 9.5 Circuit Complexity and Relativized oplus P and #P; 9.6 Relativized Polynomial-Time Hierarchy; Exercises; Historical Notes; Chapter 10 Interactive Proof Systems; 10.1 Examples and Definitions; 10.2 Arthur-Merlin Proof Systems; 10.3 AM Hierarchy Versus Polynomial-Time Hierarchy; 10.4 IP Versus AM; 10.5 IP Versus PSPACE; Exercises.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Computational complexity; Computational complexity; MATHEMATICS -- General; Computational complexity; Computational complexity; Electronic books